Shaping sustainability of seafood from capture fisheries integrating the perspectives of supply chain stakeholders through combining systems analysis tools. (20th July 2018) - Hornborg, Sara; Hobday, Alistair J; Ziegler, Friederike; Smith, Anthony D M; Green, Bridget S
Abstract: Seafood from capture fisheries can be assessed in many ways and for different purposes, with sometimes divergent views on what characterizes "sustainable use". Here we use two systems analysis tools—Ecological Risk Assessment for Effects of Fishing (ERAEF) and Life Cycle Assessment (LCA)—over the historical development of the Australian Patagonian toothfish fishery at Heard and McDonald Islands since the start in 1997. We find that ecological risks have been systematically identified in the management process using ERAEF, and with time have been mitigated, resulting in a lower risk fishery from an ecological impact perspective. LCA inventory data from the industry shows that fuel use per kilo has increased over the history of the fishery. Our results suggest that LCA and ERAEF may provide contrasting and complementary perspectives on sustainability and reveal trade-offs when used in combination. Incorporation of LCA perspectives in assessing impacts of fishing may facilitate refinement of ecosystem-based fisheries management, such as improved integration of the different perspectives of supply chain stakeholders.